(untitled) (Psychology Travelogs, 2024)
The article examines the essence of educational management and evaluates the effectiveness of its use in modern conditions of management in special institutions and inclusive resource centers. It is noted that the management of educational innovations is based on certain principles that act as norms and guidelines, in particular: humanism, democracy, national orientation, the unity of the universal and national character of education, co-creation, life creation, differentiation and individualization, optimization and openness, innovativeness. The importance of managing special institutions and inclusive resource centers is emphasized, emphasizing the need for the head to focus on purposeful and active cooperation with other participants in the educational process in order to ensure coordination of actions for the optimal functioning of the institution and increase its quality. It was determined that the quality of management in special institutions and inclusive resource centers also depends on the effective use of educational management technologies. An analysis of scientific sources was carried out, which shows that the conceptual principles of educational management are sufficiently developed in Ukraine, and the system of managing educational changes was investigated. So, in the works of F.I. Khmilya, I.L. Danylenko, M.L. Karamushki, O.I. Marmazy, N.V. Pogribnoi highlighted the problems of educational management in the conditions of innovation. The peculiarities of the activity of the education manager were reflected in the researches of G.A. Dmytrenko and L.I. Karaschuk. In their research, scientists note that modern educational management is constantly being updated, the functional composition of the manager is expanding, and new management technologies are being introduced. The peculiarities of the introduction of educational management technologies into the management system of special institutions and inclusive resource centers are considered. The organizational, information and communication aspects of the management of special institutions and inclusive resource centers are analyzed, as well as the prospects of future research in the field of the formation of a new management culture, which is necessary for the effective management of such institutions, as well as the main directions of the development of educational management in the system of inclusive education.